KORUPSI BIROKRASI (STUDI KASUS GAYUS TAMBUNAN PEGAWAI DIREKTORAT JENDERAL PAJAK) - Widiastuti, Ika (Jurnal Ilmiah Widya, 2018)
Corruption is a social parasite that damages the structure of government and is the development's main obstacle. One of the cases is Gayus Tambunan, an employee of the Directorate General of Taxation who misused his authority and position for his own interests. Bureaucratic reform is to create a professional, integrated, high-performance, free and clean government bureaucracy, able to serve the community, neutral, prosperous, dedicated, and explore the basic values ​​and code of ethics of the state apparatus. The objectives are: (1) to know and discuss bureaucratic corruption, (2) gathering information and developing the concept of bureaucratic corruption. Research method used are qualitative research, with data collection techniques using literature review. The conclusion is (1) The main difficulties for countries in countries that are part of the history of the community concerned. (2) corruption carried out by Gayus Tambunan is not only itself but also involves many people from the government and employers.